Numerical Study of Low Gain Avalanche Detector Performance - BENDIB Toufik; Brahim, Lakehal; KOUDA Souhil; Abdi Mohamed.Amir; Dendouga Abedelghani; Chebaki, Elasaad; Aouf, Anouar Essadat; Meddour Fayçal; Barra Samir (2018 International Conference on Communications and Electrical Engineering (ICCEE), 2019)
In this paper, we present a new ultra fast detector called Low Gain Avalanche Detector (LGAD) with low internal gain. The LGAD is fabricated with conventional APD technology with a modified doping profile, in the multiplication region, which affects the device performance such as: breakdown, multiplication gain and noise factor. For this reason, a numerical method based on Newton-Raphson calculation is proposed to estimate the electrostatic potential and electric field models of low gain avalanche detectors (LGADs) in order to investigate their performances. These models have been validated by their agreement with TCAD numerical simulation results. The effect of Boron doping profile, with different doses in the multiplication region, on the LGAD electrical performance is studied for various device structures in order to extend the device capability to its limit. In addition, LGAD devices are simulated for different temperature considering the effect of the temperature on the multiplication gain.